Development of a two-component recombinant vaccine for COVID-19 - Sun, Yi-Sheng; Xu, Fang; Zhu, Han-Ping; Xia, Yong; Li, Qiao-Min; Luo, Yuan-Yuan; Lu, Hang-Jing; Wu, Bei-Bei; Wang, Zhen; Yao, Ping-Ping; Zhou, Zhan (Frontiers in Immunology, 2024)
IntroductionThough COVID-19 as a public health emergency of international concern (PHEIC) was declared to be ended by the WHO, it continues to pose a significant threat to human society. Vaccination remains one of the most effective methods for preventing COVID-19. While most of the antigenic regions are found in the receptor binding domain (RBD), the N-terminal domain (NTD) of the S protein is another crucial region for inducing neutralizing antibodies (nAbs) against COVID-19.MethodsIn the two-dose immunization experiment, female BALB/c mice were intramuscularly immunized with different ratios of RBD-Fc and NTD-Fc proteins, with a total protein dose of 8 μg per mouse. Mice were immunized on day 0 and boosted on day 7. In the sequential immunization experiment, groups of female BALB/c mice were immunized with two doses of the inactivated SARS-CoV-2 vaccine (prototype strain) on day 0 and 7. On day 28, mice were boosted with RBD-Fc, NTD-Fc, RBD-Fc/NTD-Fc (9:1), RBD-Fc/NTD-Fc (3:1), inactivated SARS-CoV-2 vaccine (protoype strain), inactivated SARS-CoV-2 vaccine (omicron strain), individually. The IgG antibodies were detected using ELISA, while the neutralizing antibodies were measured through a microneutralization assay utilizing both the prototype and omicron strains. The ELISPOT assays were performed to measure the secretion of IL-4 and IFN-γ, and the concentrations of secreted IL-2 and IL-10 in the supernatants were measured by ELISA.ResultsWe have first developed a two-component recombinant vaccine for COVID-19 based on RBD-Fc and NTD-Fc proteins, with an optimal RBD-Fc/NTD-Fc ratio of 3:1. This novel two-component vaccine demonstrated the ability to induce durable and potent IgG antibodies, as well as the neutralizing antibodies in both the two-dose homologous and sequential vaccinations. Heterologous booster with this two-component vaccine could induce higher neutralizing antibody titers than the homologous group. Additionally, the vaccine elicited relatively balanced Th1- and Th2-cell immune responses.ConclusionThis novel two-component recombinant vaccine exhibits high immunogenicity and offers a potential booster strategy for COVID-19 vaccine development.